Additional education of schoolchildren in physics at the Children's University - Damekova, S.K.; Shuyushbayeva, N.N.; Tanasheva, N.K.; Altayeva, G.S.; Kaliyeva, A.K. (KU Publ., 2021)
The article describes physics projects created by students as future physics teachers to organize classes on the educational platform of the Children's University. The study was aimed at examining the performance of physics students through physics projects. The advantages of the Labster 3D virtual reality learning environment for motivating students to study physics are also considered. Generally, the results of the study showed an increase in interest among primary school students in STEM education and science. The study involved children from 10 to 12 years old in the amount of 250 schoolchildren in the city of Kokshetau (Kazakhstan). The article used methods such as mixed methods, questionnaires, and semi-structured interviews for children. The Likert scale questions allowed the analysis using descriptive statistics. Open-ended questions and data from the interviews were classified using content analysis and analytically interpreted through the theory of the development of cognitive interest in children. Children were provided by links to short 10-minute educational videos posted on Youtube video hosting called FIZMAT KSU While they were working remotely. During distance learning, children used different forms of virtual laboratory work. The results and conclusions of the study revealed the followings: visiting the Children's University increases children's interest in STEM - education and science, as well as the participation of future physics teachers in the activities of the Children's University forms the skills of organizing informal forms of work with children.
Балалар университетінде физика пəні бойынша оқушыларға қосымша білім беру
Дополнительное образование школьников по физике в Детском университете
Keywords: future physics teachers; future physics teachers; children; Children's University; experiments; virtual 3D Labster laboratory; project; STEM